Desenvolvimento do teto para a estrutura do veículo cactus baja SAE - Cavalcante, Esthefani Maria Almeida (Universidade Federal Rural do Semi-Árido, 2018)
Baja are off-road vehicles developed by university students, where they apply their theoretical knowledge to create the best prototype, and thus compete on a regional, national and global scale. The objective of this work was to study and develop the low vehicle ceiling of the Cactus Baja team. Through an analysis of the comfort of the off-road vehicle of the Cactus Baja SAE team, the possibility of producing the roof for car was seen, bringing greater comfort to the pilot and adding points of better ergonomics to the car. For the construction of the structure, materials based on tensile strength, compression, temperature, weight and ease of handling properties were studied. The composites with sisal fiber, banana fiber, carbon fiber, fiberglass and polymeric materials such as PP were analyzed because of their characteristics to suit the needs of the project and the possibility of developing a hybrid of the composites, thus being able to combine the best properties of these materials. With the help of SolidWorks CAD software, the design of the structure has been developed to improve team performance in competitions. Finite volume simulations were performed to verify the drag force in the vehicle, using Ansys software. After all the steps of bibliographic studies and simulations, enough information was obtained to select the best design and material for the preparation. The last step of this work was the confection of the structure from the studies carried out and for this the mold was developed, analyzed the relation of the resins and catalysts.
Monografia
Keywords: Materiais; Teto; Simulação; Materials; Ceiling; Simulation; ENGENHARIAS::ENGENHARIA MECANICA